Book Review: François Bourguignon and Thomas Scott-Railton (Trans.), The Globalization of Inequality. (April 2017) - Kaushal, Leena Ajit
François Bourguignon and Thomas Scott-Railton (Trans.), The Globalization of Inequality . Oxford: Princeton University Press, 2015, 210 pp., $27.95 (9780691160528) (hardback).